Structural, morphological, optical, and antimicrobial study of Mikania micrantha (leaf) extract treated zinc doped cobalt ferrite nanoparticles and antibacterial clothing applications - Abdullah Al Mahmood; Shaadnan Bin Syed; Zahid Hasan; M. Bodiul Islam; Rumana Hossain; Shamimur Rahman (Results in Surfaces and Interfaces)
To manage pathogenic diseases, different applications of nanotechnology have been harnessed to improve the antimicrobial and self-cleaning attributes of materials. The objective of this study is to examine the anti-microbial activity of silk thread; coated (ultra-sonication method) with Zn doped cobalt ferrite nanoparticles with future prospects of developing interlayer of surgical facemask or producing antibacterial wearing. The nanoparticles were synthesized following the co-precipitation method by using Mikania micrantha leaf extract. The potential antibacterial activity (against E. coli and S. aureus) of the thread as well as the nanoparticles was recorded using the Zone of Inhibition (ZOI) test result. XRD results showed the cubic crystal structure and the lattice parameter change due to Zn doping. SEM findings revealed particle agglomeration, though the particles retained an approximately spherical shape of around 52.498 nm for undoped and 32.13 nm for doped materials. FT-IR analysis confirmed that flavonoids from the leaf extract stabilized the nanoparticles. This research investigated the antibacterial capabilities of threads coated with nanoparticles; using the agar well diffusion method, the study established the robust antibacterial capabilities of the nanoparticles-coated thread. Notably, the CoFe2O4 NPs exhibited strong antimicrobial activity against specific bacterial strains, and Zn doping enhances this characteristic.